Prognostic Predictive Characteristics in Patients With Fibrosing Interstitial Lung Disease: A Retrospective Cohort Study - Wang, Yuanying; Guo, Ziyun; Ma, Ruimin; Wang, Jingwei; Wu, Na; Fan, Yali; Ye, Qiao (Frontiers in Pharmacology, 2022)
Background: Limited data are available regarding the entire spectrum of interstitial lung disease with a progressive fibrosing feature. We investigated the prevalence and prognostic predictive characteristics in patients with PF-ILD. Methods: This retrospective cohort study included patients with fibrosing ILD who were investigated between January 1, 2015 and April 30, 2021. We recorded clinical features and outcomes to identify the possible risk factors for fibrosing progression, as well as mortality. Results: Of the 579 patients with fibrosing ILD, 227 (39.21%) met the criteria for progression. Clubbing of fingers (odds ratio [OR] 1.52, 95% confidence interval [CI] 1.03 to 2.24, p=0.035) and a high-resolution computed tomography (HRCT)-documented usual interstitial pneumonia (UIP)-like fibrotic pattern (OR 1.95, 95% CI 1.33 to 2.86, p=0.001) were risk factors for fibrosis progression. The mortality was worse in patients with PF with hypoxemia (hazard ratio [HR] 2.08, 95% CI 1.31 to 3.32, p=0.002), in those with baseline diffusion capacity of the lung for carbon monoxide (DLCO)% predicted <50% (HR 2.25, 95% CI 1.45 to 3.50, p<0.001), or in those with UIP-like fibrotic pattern (HR 1.68, 95% CI 1.04 to 2.71, p<0.001). Conclusion: Clubbing of fingers and a HRCT-documented UIP-like fibrotic pattern were more likely to be associated with the progressive fibrosing with varied prevalence based on the specific diagnosis. Among patients with progressive fibrosing, those with hypoxemia, lower baseline DLCO% predicted, or UIP-like fibrotic pattern showed poor mortality.